A novel U-shaped stepping linear piezoelectric actuator with two driving feet and low motion coupling: Design, modeling and experiments. (1st June 2019) - Tian, Xinqi; Zhang, Binrui; Liu, Yingxiang; Chen, Shuo; Yu, Hongpeng
Highlights: A U-shaped stepping linear piezoelectric actuator with two driving feet is proposed. The measured output displacement motion coupling ratio of the prototype is only 4%. The developed static models can predict the step lengths and clamping force well. The prototype achieves maximum thrust force and speed of 189.7 N and 273.4 μm/s. Abstract: A U-shaped stepping piezoelectric actuator featuring low motion coupling is proposed, fabricated and tested. The actuator contains four similar piezoelectric actuation units (PAUs): two of them are used as the clamping units, while the other two act as the pushing units. The sliders and brackets supporting the clamping units can strongly suppress the motion coupling. The actuator can move the runner twice in each cycle with the operating principle similar to an inchworm. Static models are developed to calculate the step length and clamping force of the proposed actuator. A prototype is fabricated and its mechanical output characteristics are measured. The measured step length and clamping force agree well with the calculated results by the static model. The operating principle is verified by the experiment results, and the motion coupling ratio is 4%. The output speed linearly depends on the voltage applied on the pushing units, which indicates that the proposed actuator is very suitable for speed control. The working frequency has positive effect on the speed in range from 0.05 Hz to 6.25 Hz, whereas negative effect is found over 6.25 Hz. The prototype achieves a maximum thrust force of 189.7 N and a maximum speed of 273.4 μm/s.